A Development of Symptom Clusters Management Model in Lung Cancer Persons receiving Chemotherapy - Khamboon, Thidarat; Pakanta, Intira; Jitpewngam, Wittawat; Wangteeraprasert, Kittima (NU Journal of Nursing and Health Sciences, 2019)
The purpose of this study was to develop a symptom cluster management model in lung cancer patients receiving chemotherapy. The Symptom Management Conceptual Theory, and the Research and Development model were used as conceptual and methodological frameworks. The nurses educated, supported, advised, and built motivation in assessing , managing, evaluating outcome and changing the strategies to manage the symptom clusters by themselves. The research method consisted of 2 phases, as follow: 1) studying about symptom clusters in lung cancer patients, current situations, obstacles, and needs for the model in a Tertiary hospital, which was done through: non-participant observation and interviewing of lung cancer patients, who were receiving chemotherapy (20 persons) and nurses (2 persons), 2) developing a model and checking its quality by 5 experts. The data were analyzed by content validity, mean, and standard deviation. The findings showed that: 1. The most common symptom cluster of lung cancer patients receiving chemotherapy that was needed to be managed was the fatigue, loss of appetite and anxiety symptom cluster. Patients who receive general counseling about their practice, side effects of chemotherapy, and symptom management recommendations are dealt with by individual symptoms. There were no follow up when the patients got home.Patients mentioned that they needed several methods in the management of symptom cluster to enhance their knowledge based on their individual performance. In addition, they prefer to get the symptom cluster management guide book that helps to support them to continue the activity at home. They also prefer to communicate with the nurse as a consultant via phone when they are back home after they received chemotherapy for informational and emotional supports. 2. The developed model’s propriety was at a high level ( = 4.20, SD = 0.45) and feasibility was at a high level ( = 4.50, SD = 0.58). In the intervention model, nurses provided the program, gave advice and encouraged the patients to manage the symptom cluster, evaluating the results and suggested the strategies adjusting from their own ideas in controlling the symptom cluster with the methods relevant to their potential and their sickness. The nurses were following up on the patients by telephone. Therefore, the model should be tested for studying the effects of symptom cluster management model on decreasing the severity of symptom cluster and improve the quality of life in lung cancer patient receiving chemotherapy.